Dimensional Influence of Epithelialized Tissue Graft Harvested From Palate on Postoperative Pain: a Systematic Review - Mario Escobar; Renata Scheeren Brum; Karin Apaza-Bedoya; Patrícia Pauletto; Cesar Augusto Magalhães Benfatti; Ariadne Cristiane Cabral Cruz; Bruno Alexandre Pacheco Castro Henriques (Stilus Optimus, 2022)
Objectives: The aim of the present systematic review was to evaluate the dimensional influence of the epithelialized tissue graft harvested from the palate in the postoperative pain. Material and Methods: Research was conducted in electronic databases Cochrane Library, Embase, LILACS, PubMed, Scopus, and Web of Science upwards May 15, 2022. Studies that reported the influence of graft dimensions of palatal epithelized harvesting on postoperative pain were eligible. The evaluation was made using the methodological quality assessment by Joanna Briggs Institute Critical Appraisal Checklist for randomized clinical trials and non-randomized studies and the level of evidence according to GRADE. Results: Four studies were included. The clinical and methodological heterogeneity among studies led to an analysed narrative. The postoperative pain was assessed during the period of 1 to 28 postoperative days. It was determined by using visual analog score in three studies, while the evaluation was performed indirectly based on analgesics intake in one study. According to three studies, bigger graft sizes were associated with higher postoperative pain. The methodological quality assessment categorized two study as high (one randomized control trial and one non-randomized), and two as moderate (one randomized control trial and one non-randomized). The data was considered moderate. Conclusions: Based on the moderate certainty level, bigger graft sizes of palatal epithelized harvesting appear to promote more postoperative pain. Understanding the postoperative pain as a response to a graft extension may assist some clinical decisions regarding the surgical periodontal and peri-implant planning.